Design and performance testing of a novel emergency ventilator for in-hospital use. - Knorr, Jacob M.; Sheehan, Megan M.; Santana, Daniel C.; Samorezov, Sergey; Sammour, Ibrahim; Deblock, Michael; Kuban, Barry; Chaisson, Neal; Chatburn, Robert L. (Canadian Journal of Respiratory Therapy, 2020)
Background: The rapidly evolving COVID-19 pandemic has led to increased use of critical care resources, particularly mechanical ventilators. Amidst growing concerns that the health care system could face a shortage of ventilators in the future, there is a need for an affordable, simple, easy to use, emergency stockpile ventilator. Methods: Our team of engineers and clinicians designed and tested an emergency ventilator that uses a single limb portable ventilator circuit. The circuit is controlled by a pneumatic signal with electronic microcontroller input, using air and oxygen sources found in standard patient rooms. Ventilator performance was assessed using an IngMar ASL 5000 breathing simulator, and it was compared with a commercially available mechanical ventilator. Results: The emergency ventilator provides volume control mode, intermittent mandatory ventilation and continuous positive airway pressure. It can generate tidal volumes between 300 and 800 mL with <10% error, with pressure, volume, and waveforms substantially equivalent to existing commercial ventilators. Conclusions: We describe a cost effective, safe, and easy to use ventilator that can be rapidly manufactured to address ventilator shortages in a pandemic setting. It meets basic clinical needs and can be provided for emergency use in cases requiring mechanical ventilation because of complications due to respiratory failure from infectious diseases.